2-Methylimidazole directed ambient synthesis of zinc-cobalt LDH nanosheets for efficient oxygen evolution reaction - Qiu, Chunyu; Cai, Fuxian; Wang, Yuan; Liu, Yijun; Wang, Qingxiang; Zhao, Chuan (Journal of colloid and interface science, 2020)
[Display omitted] It is a highly desired yet challenging task to replace rare and expensive noble metal catalysts with inexpensive and earth-abundant metal ones in electrochemical sustainable chemistry field. Herein, the bimetallic zinc-cobalt layered double hydroxide nanosheets (ZnCo-LDH NS) have been facilely synthesized using 2-methylimidazole as a bifunctional alkali source (OH−) and a morphological controlling reagent by the one-step room-temperature reaction. The mechanism study shows that the weak organic base of 2-methylimidazole-induced slow release of OH− in water/ethanol is the controlling factor for the formation of the LDH nanosheets. The ZnCo-LDH NS modified on glassy carbon electrode exhibited an overpotential of 385 mV at 10 mA cm−2 and a Tafel slope of 108 mV dec−1 in 1.0 M KOH for oxygen evolution reaction, outperforming the corresponding the monometal oxides of Zn-OH, Co-OH, the NaOH produced ZnCo-LDH microparticles, and even the benchmark catalyst of RuO2 at high current density. Characterization experiments indicated that the outstanding electrocatalytic activity can be ascribed to the nanosheet-induced surface area effect, excellent electronic conductivity, and the coupling effect between Zn2+ and Co2+ in the material. This work offers a facile and environmental-friendly method for synthesising LDH nanosheets bearing enhanced oxygen evolution reaction activity.